JSCC Recommended Method for Glycated Albumin Measurement in Serum - Takei Izumi; 星野 忠夫; 富永 真琴; 中山 年正; 桑 克彦; 梅本 雅夫; 谷 渉; 岡橋 美貴子; 松尾 雄志; 谷口 嘉之; 石橋 みどり; 渡辺 直美; et al. (Japanese Journal of Clinical Chemistry, 2008)
Measurement of glycated albumin (GA) has been introduced into clinical laboratory medicine as a new marker for diabetes, and it is now widely used as a routine test in Japan. However, due to absence of a reference measurement method, it was necessary to promptly establish a standardized procedure. Since 2002, the following activities have been conducted as part of the GA standardization project: 1) a survey of the actual conditions to understand the current status of GA measurement; 2) a basic study to define GA; 3) preparation of reference materials and establishment of a reference method; and 4) determination of reference intervals.The basic study to define GA involved peptide mapping, since albumin has multiple glycation sites and it was necessary to determine suitable glycation sites exist in GA. Based on these results, in the present study, GA was defined as “albumin containing lysine residues bound to glucose (NE(1-deoxy-D- fructos- 1-yl)-L-lysine: DOF-Lys) ” A method based on isotope dilution mass spectrometry (ID-MS) is proposed as the reference measurement procedure to be used as a traceable tool of GA standardization. Herein, we present the ID-MS procedure and its performance results.Methods: After isolating albumin from serum, stable isotopes of DOF-Lys and lysine (Lys) were added to albumin fractions as internal standards and glycation sites were subject to hydrogenation followed by hydrolysis. All freed DOF-Lys and Lys residues were recovered by reduced pressure drying, and their isotopic ratios were determined using liquid chromatography-mass spectrometry. GA levels were expressed in terms of molar ratios (unit: mmol/mol) of all liberated DOF-Lys residues and albumin calculated from all liberated Lys residues.Results: The measurement precision of the present method was CV 1.2% for within-run reproducibility (n=10) and CV 1.4% for day-to-day reproducibility (n=15); favorable compatibility with routine tests (r=0.996) was demonstrated.Conclusion: The present ID-MS method of GA. measurement is a valid reference measurement procedure for GA.